Non-Coding RNAs in Sepsis-Associated Acute Kidney Injury - Chen, Yanna; Jing, Huan; Tang, Simin; Liu, Pei; Cheng, Ye; Fan, Youling; Chen, Hongtao; Zhou, Jun (Frontiers in Physiology, 2022)
Sepsis is a systemic inflammatory response caused by a severe infection that leads to multiple organ damage, including acute kidney injury (AKI). In intensive care units (ICU), the morbidity and mortality associated with sepsis-associated AKI (SA-AKI) are gradually increasing due to lack of effective and early detection, as well as proper treatment. Non-coding RNAs (ncRNAs) exert a regulatory function in gene transcription, RNA processing, post-transcriptional translation, and epigenetic regulation of gene expression. Evidence indicated that miRNAs are involved in inflammation and programmed cell death during the development of sepsis-associated AKI (SA-AKI). Moreover, lncRNAs and circRNAs appear to be an essential regulatory mechanism in SA-AKI. In this review, we summarized the molecular mechanism of ncRNAs in SA-AKI and discussed their potential in clinical diagnosis and treatment.